2018
DOI: 10.1111/bjh.15695
|View full text |Cite
|
Sign up to set email alerts
|

Novel therapeutic agents for relapsed classical Hodgkin lymphoma

Abstract: Summary Hodgkin Lymphoma (HL) is a B‐cell lymphoproliferative disorder with an excellent prognosis for the majority of patients who are treated with multi‐agent chemotherapy, with or without radiation. A subset of patient, however, does not respond to therapy or relapses after accomplishing an initial response. Their outcome is poor and new treatment strategies are urgently needed for this patient population. Recent advances in the understanding of the tumour biology of HL and its microenvironment have ushered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 63 publications
(67 reference statements)
0
9
0
Order By: Relevance
“…13,14 Recently, a better understanding of the complex and unique cHL biology 15 paved the way for the development of biology-driven therapies and a few new drugs with remarkable efficacy and acting by diverse and novel mechanisms of action have become available in clinical practice. 16 This scenario has ushered in a new treatment era and has opened new perspectives for improving the outcome of RR-cHL patients. 13,17,18 Among new drugs, bendamustine (b) (Moskowitz et al 19 ; El Cheikh et al 20 Corazzelli et al 23 ) and brentuximab vedotin (Bv) [24][25][26][27][28] showed high efficacy and manageable toxic effects in heavily pretreated patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…13,14 Recently, a better understanding of the complex and unique cHL biology 15 paved the way for the development of biology-driven therapies and a few new drugs with remarkable efficacy and acting by diverse and novel mechanisms of action have become available in clinical practice. 16 This scenario has ushered in a new treatment era and has opened new perspectives for improving the outcome of RR-cHL patients. 13,17,18 Among new drugs, bendamustine (b) (Moskowitz et al 19 ; El Cheikh et al 20 Corazzelli et al 23 ) and brentuximab vedotin (Bv) [24][25][26][27][28] showed high efficacy and manageable toxic effects in heavily pretreated patients.…”
Section: Introductionmentioning
confidence: 99%
“…In such patients, conventional chemotherapy results in very poor outcomes, allowing a median OS of around 25 months . Recently, a better understanding of the complex and unique cHL biology paved the way for the development of biology‐driven therapies and a few new drugs with remarkable efficacy and acting by diverse and novel mechanisms of action have become available in clinical practice . This scenario has ushered in a new treatment era and has opened new perspectives for improving the outcome of RR‐cHL patients .…”
Section: Introductionmentioning
confidence: 99%
“…Most notably, the antibody-drug conjugate brentuximab vedotin and the immune checkpoint blockers pembrolizumab and nivolumab have been approved recently by the US Food and Drug Administration. 24 For developing countries, however, the use of novel therapies is limited because of cost issues.…”
Section: Discussionmentioning
confidence: 99%
“…The prognosis for patients with cHL that are relapsing/refractory (r/r) after first-line treatment or autologous stem cell transplantation (ASCT) is very poor ( 3 ). About 10–40% of patients do not achieve a response to salvage chemotherapy and no randomized clinical trial data support ASCT in non-responders ( 4 ). Therefore, it is imperative to develop novel approaches to improve the prognosis for patients with r/r cHL.…”
Section: Introductionmentioning
confidence: 99%